2020
DOI: 10.3390/agronomy10122009
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Drainage Waters Collected during Soilless Tomato Cultivation in Mineral and Organic Substrates

Abstract: The aim was to determine the suitability of various substrates for application in a closed system of soilless tomato cultivation, based on the potential fitness of drainage waters from these substrates for recirculation. Four substrates were used: rockwool, coir substrate, lignite substrate (Carbomat) and biodegradable organic substrate (Biopot). Tomato plants grown in these substrates were fertilized with the same amount of nutrient solution, containing the same concentration of nutrients. The characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…La conductividad eléctrica fue de 0.282 y 3.08 dS m -1 y el pH fue de 7.59 y 7.06 para el agua y el sustrato, respectivamente. Dyśko et al (2020) usaron lana roca como sustrato en tomate con pH de 7.5 y observaron mayor rendimiento de frutos. Melo et al (2019) utilizaron sustrato de fibra de coco con pH 6.0 y reportaron mayor materia seca de planta y raíz en tomate.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…La conductividad eléctrica fue de 0.282 y 3.08 dS m -1 y el pH fue de 7.59 y 7.06 para el agua y el sustrato, respectivamente. Dyśko et al (2020) usaron lana roca como sustrato en tomate con pH de 7.5 y observaron mayor rendimiento de frutos. Melo et al (2019) utilizaron sustrato de fibra de coco con pH 6.0 y reportaron mayor materia seca de planta y raíz en tomate.…”
Section: Resultados Y Discusiónunclassified
“…Melo et al (2019) utilizaron sustrato de fibra de coco con pH 6.0 y reportaron mayor materia seca de planta y raíz en tomate. El pH del sustrato que se utilizó en el experimento se encuentra dentro de los valores reportados por Melo et al (2019) y Dyśko et al (2020).…”
Section: Resultados Y Discusiónunclassified
“…In South Korea, crops cultivated in a system with nutrient medium recirculation account for 5% of the 3355 arable hectares [32]. According to Dyśko et al [33], the open-circuit system is still the main method for growing tomatoes in Poland, while recirculation is deployed only in a few facilities growing vegetables, including mainly those producing low biomass and requiring low variability of the nutrient medium composition [33].…”
Section: Open-circuit Systemsmentioning
confidence: 99%
“…In a study by Muñoz et al [26], the volume of DW discharged from tomato cultivation was 207.9 and 219.0 L/m 2 at 28% and 39% overflow, respectively. In turn, Dyśko et al [33] reported that 6-month tomato cultivation on mineral wool in the open-circuit system produced 3082 m 3 /ha of the overflow.…”
Section: Open-circuit Systemsmentioning
confidence: 99%
“…The crops are mainly fertilized in open systems [5]. According to Dyśko et al [6], 70% of the medium supplied is used by plants, with the remaining 30% being used as overflow and discharged, untreated, into the environment. According to the regulations in Poland, horticultural effluent should be treated, and the nitrogen and phosphorus levels, before being discharged to the environment, should not exceed 30 mg N/L and 3 mg P/L [5,7,8].…”
Section: Introductionmentioning
confidence: 99%